The silent signal of widened pulse pressure-aortic dissection in pregnancy - Subramaniam, Kaithri Devi; Daud, Shasheila M.; Amin, Rafaie (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2025)
Aortic dissection in pregnancy is a rare but potentially life-threatening condition, often presenting with non-specific symptoms that can hinder timely diagnosis. Stanford type A dissections are especially perilous, with high risks of maternal and fetal mortality if not promptly treated with surgical intervention. A 35-year-old woman, G3P2 at 39 weeks’ gestation, presented with sudden-onset epigastric pain. Her blood pressure was 103/43 mmHg, with a widened pulse pressure of 60 mmHg - a subtle yet significant indicator. The initial examination was unremarkable however an urgent echocardiography and CT aortography confirmed a Stanford type A aortic dissection, extending from the aortic root to the infrarenal abdominal aorta. An urgent interdisciplinary discussion (MDT) was convened. Given the complexity of the case, which required the expertise of a highly experienced cardiothoracic surgeon, a surgeon was flown in from Peninsular Malaysia. She was transferred to the Sarawak Heart Centre, where she underwent an emergency caesarean section, delivering a baby boy weighing 2.7 kg. This was followed by a 13-hour Bentall procedure and coronary artery bypass grafting. Although the surgery was technically successful, she sadly succumbed to postoperative heart failure seven hours later. This case highlights the importance of early recognition and timely intervention in aortic dissection during pregnancy. Although rare, pregnancy associated aortic dissection carries significant risks for both mother and fetus. Despite the tragic outcome, the swift and coordinated response by the multidisciplinary team is commendable and reflects their commitment in providing high-risk care in a challenging and resource-limited setting.